Description and Factors Related of Risk Assessment of Chronic Obstructive Pulmonary Disease in Community Setting - Marita Fadhilah; Raka Prazasta (The Avicenna Medical Journal, 2020)
Background: Currently, Chronic Obstructive Pulmonary Disease (COPD) is one of degenerative disease with high morbidity and mortality, especially in low-income countries, including Indonesia. Increasing prevalence of COPD in Indonesia straightly correlates with increasing of tobacco smoking and air pollution level. Many studies had conducted to decrease COPD morbidity and mortality. Prevention is the best way to reduce the incidence of COPD. This study aimed to identify risk assessment of COPD in the community around Research, Teaching, and Clinical Unit (RTCU) Buaran, South Tangerang.Methods: This study was cross sectional design and involved 134 respondents (41 males and 93 females) who live around RTCU Buaran, using two stages cluster sampling. During April to June 2015, respondents were asked to fill the questionnaire that adapted from COPD Risk Screener that contains five questions.Results: The study showed that the risk assessment of COPD of community around RTCU Buaran was 5.2% at high risk and 94.8% at low risk respectively. Using Fisher's Exact Test, there was signicant correlation between the risk assessment of COPD and respondents' age, gender, the early symptoms of COPD, and tobacco smoking (p<0.05).Conclusion: This study showed the risk assessment of COPD of community around RTCU Buaran was dominantly at low risk (94.8%), it seemed due to females' respondents more dominant than males'. Factors that significantly related to risk of COPD were age, gender, the early symptoms of COPD, and tobacco smoking.